Out-of-School Sports Participation Is Positively Associated with Physical Literacy, but What about Physical Education? A Cross-Sectional Gender-Stratified Analysis during the COVID-19 Pandemic among High-School Adolescents - Mirela Sunda; Barbara Gilic; Damir Sekulic; Radenko Matic; Patrik Drid; Dan Iulian Alexe; Gheorghe Gabriel Cucui; Gabriel Stanica Lupu (MDPI AG, 2022)
Physical literacy (PL) is one of the main concepts related to lifelong physical activity (PA) and physical fitness (PF), but there is a lack of information on factors that might be associated with PL in adolescents from southeastern Europe. This study aimed to evaluate the associations between PF, participation and achievement in physical education (PE), out-of-school participation in sports, and PL in high school adolescents from Croatia. Participants were 298 high school students aged 14-18 years (191 females). Variables included school age, PE grade, sports participation, anthropometric indices, four PF tests, and PL (evidenced by CAPL-2-knowledge and understanding questionnaire (CAPL-2-KU) and PLAYself questionnaire). Gender-stratified analyses of differences were conducted using the t-test for independent samples or the Mann-Whitney test. Associations between variables were calculated with Pearson's product moment correlation or Spearman's rank order correlation. PF was positively correlated CAPL-2-KU in both genders. PE grade was significantly associated with PLAYself score (Pearson's correlation = 0.36 and 0.38, p < 0.001 for boys and girls, respectively) but not with the CAPL-2-KU score. School age was not correlated with PL among boys, but there was a significant but negligible correlation between CAPL-2-KU and school age in girls (<2% of the common variance). Adolescents involved in sports had better PL and PF compared with adolescents not involved in sports. In conclusion, participation in out-of-school sports offers a good base for developing PL. Although this study took part over the COVID-19 pandemic period when the regular PE curriculum was significantly altered, the poor associations between school age and PL could lead to the assumption that the current PE curriculum does not allow for improvement of PL in later high school age, which warrants further investigation.